Volatility, expiration day effect and pricing efficiency: evidence from the Kuala Lumpur composite index futures - Fauzias Mat Nor; Tea, Lee Choo (Penerbit Universiti Kebangsaan Malaysia, 2002)
A study was conducted on issues related to the introduction and trading of Kuala Lumpur Composite Index futures contract in Malaysia. Issues related to volatility, expiration day effect and pricing efficiency were examined. The test (using Levene test) indicated that a decrease in volatility was observed after the futures trading. Most stocks show a significant decrease in volatility in the post-futures period than their non-KLCI components. These noted changes were not uniform and were dependent upon individual stocks and industry sectors. It might be due to the existence of futures market which led to a stability effect by increasing information flow and market liquidity, as well as by reducing market risk by providing hedging opportunities. It is concluded that futures volatility is significantly higher, especially where there are big price movements of the underlying assets. No evidence of any expiration day effect was found. The test of mispricing shows frequent underpricing than overpricing. If transaction costs is included, it shows very little mispricing